Biodegradation rate of biodegradable plastics at molecular level - Chinaglia, Selene; Tosin, Maurizio; Degli-Innocenti, Francesco (Polymer degradation and stability, 2018)
Plastics are solid materials where biodegradation happens on the surface. Only the surface is affected by biodegradation while the inner part should not be readily available for biodegradation. Thus, at a laboratory level, the biodegradation rate is expected to be a function of the surface area of the tested sample. The higher the surface area, the higher the biodegradation rate, all other environmental conditions being equal. In order to further explore the role of particle size on biodegradability, plastic pellets of polybutylene sebacate were milled and sieved into different particle sizes, thus obtaining four samples, pellets included, with different specific surface areas (33, 89, 193, and 824 cm2g-1). The surface areas were assessed through direct measurement (pellets) or a theoretical estimation followed by an image analysis. The different samples were tested for biodegradation in soil for 138 days. The rates calculated with a linear regression in the first part of the biodegradation process were related to the respective total available surface area. The data are well described by a linear regression of the double reciprocal plot (the Lineweaver-Burk approach used in enzymatic kinetics) that enables the estimation of the theoretical maximum biodegradation rate (kmax = 97 mg Cpolymer day−1). The kmax can be considered as an estimation of the biodegradation rate at molecular level, when the available surface area is not limiting biodegradation. An additional hypothesis is that the same polymer tested in soils with different microbial loads would display different kmax. The Michaelis constant (Km), i.e. the surface area at which the reaction rate k is half the maximum rate, is 1122 cm2. It is remarkable to notice that if polybutylene sebacate could be tested in a nanopolymeric form, it could very likely satisfy the Organization for Economic Co-operation and Development (OECD) criteria of “ready biodegradability” for chemicals (e.g. 60% biodegradation in a 10-day window within a 28-day test). This is the first time that the biodegradation kinetics of a solid polymer have been estimated by using the Michaelis-Menten approach. •This is one of the few systematic studies where the effect of granulometry on biodegradation rate is tackled experimentally.•The surface area and biodegradation rate are well correlated by a double reciprocal model (the Lineweaver-Burk plot).•The maximum biodegradation rate of the polymer when surface area is not a limiting factor was estimated to be very high.•If the polymer were tested in a nanopolymeric form it could satisfy the OECD “ready biodegradability” for chemicals.Ready biodegradable chemicals are expected to undergo biodegradation in any biologically-active environment.